La Convivencia Escolar: una alternativa desde las historias de vida escolares para la resolución de conflictos en estudiantes del grado décimo del colegio Instituto Superior Cooperativo. 2022. - Cortés Cárdenas, Laura Lizeth (Universidad Antonio Nariño, 2022)
School coexistence in Colombia is a reflection of the daily practices that each of the studen ts carries out in the different educational spaces, evidencing their dynamics within their own context, which adheres to the entire set of relationships and behaviors. From this it can be evidenced that school coexistence is affected by problems ranging fr om situations such as school violence, poor academic performance, individualism, school dropout, etc. In order to mitigate this problem and provide an alternative, in the development of this work the proposal of a didactic unit will be traced that ha stories for the recovery of values s the purpose of building school life such as respect, tolerance, empathy, fraternity, among others, to reduce those conflicts that affect school coexistence. In this document you will find the due process of how the didactic unit was structured, its components through the realization of modules and later its implementation